BANK HEALTH ANALYSIS BEFORE AND AFTER X RECAPITALIZATION VIEWED FROM EQUITY CAPITAL FACTORS, QUALITY OF PRODUCTIVE ASSETS, PROFITABILITY AND LIQUIDITY - Soegijanto Soegijanto (JAKSTIK Journal, 2005)
With the deregulation of Banking conducted by the government through June 1, 1983package which gives freedom to banks in determining credit limits provided within itscapabilities and determine the interest rates of deposits and savings. October 27, 1998package provides ease in setting up the opening of the Bank and Branch. From both of thesepackages have an impact on the increasing number of banks (both head office and branches),so the competition to attract funds from the public has increased.Bank Indonesia as a supervisor and coach of the National Banking require control of the bank- a bank it to know the financial condition and operations of each bank. Bank Indonesia, helda regular basis by assessing the supervision standard tehadap bank soundness based oninformation from reports such as balance sheet along with the administrative account, the listof securities held and issued, details of loans, investment details, details of profit and lossstatements and other health lain.Tingkat bank is the interest of all parties involved, both theowner and manager of the bank, community bank service users, as well as Bank Indonesia asthe National Banking supervisors and coaches.Bank health assessment can be done with qualitative and quantitative approach to calculationof the most influential aspect of the condition and development of a bank that includesassessment of the capital factor (capital), quality of productive assets (assets), management(managerial), profitability (Earning Power) , liquidity (Liquidity), commonly called CAMEL,which can be determined from the results of the assessment of health of a bank predicate.For banks that get a bad title, but can meet the requirements specified by the Governmentmay be included daam Recapitalization programs, thus increasing the value of its CapitalAdequacy Ratio.